Kinerja Pegawai: Kecerdasan Emosional dan Sikap Kerja - Subandrio, Subandrio; AP, M Galy Njoman; Bahrun, Khairul (Fakultas Ekonomi, Universitas Semarang, 2024)
The quality and competence of human resources are key aspects that influence organizational success and a company's ability to design strategies to compete in an increasingly competitive market. The purpose of this study is to determine whether emotional intelligence and work attitude affect employee performance at the Secretariat of the Regional House of Representatives (DPRD) of Seluma Regency. This study is categorized as quantitative research, with a population encompassing all employees at the Secretariat of DPRD Seluma Regency, totaling 50 employees. A sample of 48 individuals was used, selected through a saturated sampling approach. Two independent variables (X) were used: emotional intelligence and work attitude, while the dependent variable (Y) was employee performance. The data was collected as primary data through directly distributed questionnaires. The data analysis technique employed was multiple linear regression, processed using SPSS version 26, which included validity testing, reliability testing, classical assumption testing, and hypothesis testing. The research results indicate that emotional intelligence has a positive and significant effect on employee performance, meaning that the better employees manage their emotional intelligence, the higher their performance. Additionally, work attitude also has a positive and significant impact on performance, showing that an increase in emotional intelligence and work attitude among employees will enhance their performance.